The Effect of Service Quality and Responsiveness on Customer Satisfaction on the Purchase of Wardah Facial Wash Official Store on Shopee E-commerce - Dhama Tri Febriyati; Hardi Fernando (DEAL: International Journal of Economics and Business, 2024)
This study aims to analyze the influence of service quality and responsiveness on customer satisfaction on the purchase of Wardah Facial Wash on Shopee. In the world of e-commerce, service quality includes reliability, responsiveness, guarantees, empathy, and physical evidence which are the keys to success in building customer satisfaction. In addition, responsiveness, which reflects the speed and accuracy of responding to customer needs, is an important dimension in creating a positive shopping experience. This study uses a quantitative approach with a survey method. The data was obtained through an online questionnaire to customers who had purchased Wardah products on Shopee, using the Likert scale to measure variables. The sampling technique was carried out by purposive sampling of respondents who met certain criteria. Data analysis was carried out using SmartPLS software to test the validity, reliability, and relationships between variables. The results show that service quality and responsiveness have a significant positive influence on customer satisfaction, where service quality contributes more than responsiveness. The R-Square test revealed that these two variables together are able to explain almost half of the variation in customer satisfaction. These findings emphasize the importance of strategies to improve service quality and responsiveness to strengthen customer loyalty. Companies are advised to continuously improve service dimensions such as reliability and responsiveness to create a superior shopping experience. The practical implications of these results provide strategic insights for Wardah in maintaining its competitive position in an increasingly dynamic e-commerce market.